DIGITAL TRANSFORMATION THROUGH SHOPEE PLATFORM OPTIMIZATION TO ENHANCE RECYCLED PRODUCT INNOVATION AND MARKET COMPETITIVENESS - Karno Diantoro; Ahmad Soderi; Juwari (Yayasan Nuraini Ibrahim Mandiri, 2025)
This study stems from the low level of digital literacy among recycled product entrepreneurs in Kelurahan Baktijaya, Depok, which limits their access to online markets. The research aims to enhance digital competencies and expand marketing channels through targeted training on utilizing the Shopee platform. A descriptive qualitative method was employed within a community engagement framework, using data collected from observations, pre-tests, post-tests, and documentation. The participants were members of the bank sampah community in RW 18 and RW 19. Findings reveal a substantial increase in digital understanding and operational skills, alongside heightened awareness of incorporating sustainability narratives into product promotion. The study confirms that community-based training can effectively foster digital transformation and strengthen green entrepreneurship rooted in circular economy principles.